2000
DOI: 10.1046/j.1439-0507.2000.00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Cryptococcus activity of combination of extracts of Cassia alata and Ocimum sanctum

Abstract: The paper reports the anti-Cryptococcus activity of combination of ethanolic extracts of leaves of Cassia alata and Ocimum sanctum. The activity of combination of the extracts was heat-stable and worked at acidic pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 7 publications
(11 reference statements)
1
10
0
Order By: Relevance
“…Folklore claims that O. sanctum possesses some antiseptic and antimicrobial activity. There are numerous reports regarding the antimicrobial activity of this plant [3]. In our previous study, various extracts of leaves of O. sanctum exhibited considerable activity against N. gonorrhoeae [4].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Folklore claims that O. sanctum possesses some antiseptic and antimicrobial activity. There are numerous reports regarding the antimicrobial activity of this plant [3]. In our previous study, various extracts of leaves of O. sanctum exhibited considerable activity against N. gonorrhoeae [4].…”
Section: Introductionmentioning
confidence: 81%
“…In addition, five clinical isolates (1)(2)(3)(4)(5) were used to test the activity during bioassay-guided purification, as some of the purified fractions were not available in sufficient amount to be tested on a larger number of isolates. The activity of the characterised active fraction (H12c) was tested on 14 other isolates (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Neisseria Gonorrhoeae Clinical Isolates and World Health Orgmentioning
confidence: 99%
See 1 more Smart Citation
“…Cassia alata leaves are also reported to possess anti-inflammatory, antimutagenic, analgesic and antimicrobial properties (Khan et al, 2001;Villasenor et al, 2002;Somchit et al, 2003). Further Cassia alata extract showed anti-cryptococcus activity when used in combination with Ocimum sanctum extract (Ranganathan and Balajee, 2000). Chemical constituents of Cassia alata includes phenolics (chrysaphanol, emodin, rhein, aloe-emodin, kaempferol and their glycosides), fatty acids (palmitic, oleic, linoleic acids), terpenoids (␤-sitosterol, stigmasterol, campesterol) and anthraquinones (alatonal, alatinone) (Khare, 2007;Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been reported on the in vitro antimalarial activity of terpenes (Kalauni et al, 2006;Suksarman et al, 2006;Chukwejeku et al, 2005), on biological activities of Ocimum gratissimum essential oil (Ueda-Nakamura et al, 2006;Tchoumbougnang et al, 2005;Usip et al, 2006) and on antimicrobial activity of aqueous and ethanol extracts of Cassia alata (Somchit et al, 2003;Villasenor et al, 2002;Ranganathan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%